Natural convection in a vertically divided square enclosure by a solid partition into air and water regions - Öztop, Hakan Fehmi; Varol, Yasin; Koca, Ahmet (Pergamon-Elsevier Science Ltd, 2009)
Numerical analyses of the flow and heat transfer due to buoyancy forces in a square enclosure divided by an impermeable partition between air and water filled chests were carried out using a finite difference technique. The enclosure was heated from left wall and cooled from right, isothermally. Horizontal walls were adiabatic. The partition divided the enclosure into air and water regions. Thus, two cases were examined: left side of partition was filled with air and right side was filled with water (Case I, air-partition-water) and left side was filled with water and right side with air (Case II, water-partition-air). Epoxy was chosen as partition material. Results were obtained for different Grash of numbers (10(3) <= Gr <= 10(6)), thickness of the partition (0.05 <= epsilon <= 0.2) and location of the partition (0.25 <= c <= 0.75). An analytical treatment has been performed for low Grash of numbers. Numerical and analytical results gave an acceptable agreement. It was found that filling of fluid into chests is important for obtaining maximum heat transfer and energy saving. When left chest was filled with air (Case I), higher heat transfer was formed. It was an interesting result that heat transfer decreased with increasing of location of the partition for all values of partition thickness at Case I. On the contrary, heat transfer was a decreasing function of increasing value of location of the partition. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Heat transfer; Partition; Fluid